The effect of lactoferrin supplementation on death or major morbidity in very low birthweight infants (LIFT): a multicentre, double-blind, randomised controlled trial. (June 2020) - Tarnow-Mordi, William O; Abdel-Latif, Mohamed E; Martin, Andrew; Pammi, Mohan; Robledo, Kristy; Manzoni, Paolo; Osborn, David; Lui, Kei; Keech, Anthony; Hague, Wendy; Ghadge, Alpana; Travadi, Javeed; et al.
Summary: Background: Very low birthweight or preterm infants are at increased risk of adverse outcomes including sepsis, necrotising enterocolitis, and death. We assessed whether supplementing the enteral diet of very low-birthweight infants with lactoferrin, an antimicrobial protein, reduces all-cause mortality or major morbidity. Methods: We did a multicentre, double-blind, pragmatic, randomised superiority trial in 14 Australian and two New Zealand neonatal intensive care units. Infants born weighing less than 1500 g and aged less than 8 days, were eligible and randomly assigned (1:1) using minimising web-based randomisation to receive once daily 200 mg/kg pasteurised bovine lactoferrin supplements or no lactoferrin supplement added to breast or formula milk until 34 weeks' post-menstrual age (or for 2 weeks, if longer), or until discharge from the study hospital if that occurred first. Designated nurses preparing the daily feeds were not masked to group assignment, but other nurses, doctors, parents, caregivers, and investigators were unaware. The primary outcome was survival to hospital discharge or major morbidity (defined as brain injury, necrotising enterocolitis, late-onset sepsis at 36 weeks' post-menstrual age, or retinopathy treated before discharge) assessed in the intention-to-treat population. Safety analyses were by treatment received. We also did a prespecified, PRISMA-compliant meta-analysis, which included this study and other relevant randomised controlled trials, to estimate more precisely the effects of lactoferrin supplementation on late-onset sepsis, necrotising enterocolitis, and survival. This trial is registered with the Australian and New Zealand Clinical Trials Registry, ACTRN12611000247976. Findings: Between June 27, 2014, and Sept 1, 2017, we recruited 1542 infants; 771 were assigned to the intervention group and 771 to the control group. One infant who had consent withdrawn before beginning lactoferrin treatment was excluded from analysis. In-hospital death or major morbidity occurred in 162 (21%) of 770 infants in the intervention group and in 170 (22%) of 771 infants in the control group (relative risk [RR] 0·95, 95% CI 0·79–1·14; p=0·60). Three suspected unexpected serious adverse reactions occurred; two in the lactoferrin group, namely unexplained late jaundice and inspissated milk syndrome, but were not attributed to the intervention and one in the control group had fatal inspissated milk syndrome. Our meta-analysis identified 13 trials completed before Feb 18, 2020, including this Article, in 5609 preterm infants. Lactoferrin supplements significantly reduced late-onset sepsis (RR 0·79, 95% CI 0·71–0·88; p<0·0001; I 2 =58%), but not necrotising enterocolitis or all-cause mortality. Interpretation: Lactoferrin supplementation did not improve death or major morbidity in this trial, but might reduce late-onset sepsis, as found in our meta-analysis of over 5000 infants. Future collaborative studies should use products with demonstrated biological activity, be large enough to detect moderate and clinically important effects reliably, and assess greater doses of lactoferrin in infants at increased risk, such as those not exclusively receiving breastmilk or infants of extremely low birthweight. Funding: Australian National Health and Medical Research Council.